(untitled) (CIPEEX, 2025)
Physical inactivity is a significant public health concern among adolescents, with three out of four failing to meet the recommended levels of physical activity (PA). This scenario stems from various barriers that hinder engagement in regular PA. To assess the effectiveness of interventions aimed at reducing barriers to PA participation in adolescents. This is a systematic literature review structured according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020). Searches were conducted in five databases: PubMed, SPORTDiscus, Embase, Scopus, and Web of Science. Thirty-four studies explored interventions to overcome barriers to PA, addressing lack of motivation, support, and intrapersonal, interpersonal, and environmental obstacles. Most studies were conducted in developed countries, with a particular focus on girls, aiming to reduce health inequalities. The interventions—implemented mainly in schools—included workshops, training sessions, lectures, goal setting, and practical activities, lasting from four weeks to four years. Twenty-seven studies (79.4%) reported positive outcomes, especially those addressing psychosocial, psychological, and behavioral barriers. The most effective interventions combined theoretical (educational approaches) and practical (activity-based) components. This systematic review, which included studies on barriers to physical activity among adolescents, highlights the effectiveness of diverse approaches, such as adapted school programs and educational campaigns. These strategies are crucial for overcoming obstacles like demotivation and lack of encouragement, promoting greater adolescent participation in PA and significant improvements in overall health.